The Study Of EFL Students' Extensive Listening Activities At University Of Islam Malang - Trisnawati Hasdiah Rahman (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Listening is a basic language skill that is important in receiving oral messages to carry out communication with others more effectively. However, mastering listening especially in the EFL context requires a lot of practice, therefore language learners need to carry out extensive listening practice outside of class activities. Extensive listening can be defined as listening for pleasure that allows learners to receive both comprehensive and enjoyable input. Due to this reason, the researcher is interested in studying EFL students’ extensive listening activities at the university. This study was carried out using descriptive qualitative research methods through questionnaires and semi-structured interviews as an instrument. The questionnaire is used to find 5 suitable participants for the interview from the students of the English department at the University of Islam Malang. The data for this research was collected online through the use of WhatsApp voice notes and video calls. The result of the interview is analyzed using qualitative analysis for more detailed data about extensive listening activities. The result showed that all students have a medium to a high level of perception towards both aspects of extensive listening such as enjoyment and benefit and give positive responses towards six kinds of extensive listening material such as English songs, movies, podcasts, audio, news, and speech. The result also indicated that extensive listening has many benefits, such as providing an enjoyable learning experience and environment, flexibility to be used anywhere anytime, and flexibility to choose material based on learning purpose and needs. Moreover, extensive listening also benefits language skills such as vocabulary, pronunciation, retention, comprehension, authentic material, and more importantly improvement in listening skills. Keywords: Listening Skill, Extensive Listening Activities